Умножение минус на минус даст в ответе плюс.
(- 6 3/4) * (- 1 11/45) = -27/4 * (- 56/45) =
= ( - 27 * - 56)/ (4 * 45) = 126/15 = 8 6/15 = 8 2/5.
1/(3b-5)-1/(3b+5))* (9b²-25)=
=(3b+5-3b+5)/(3b-5)(3b+5) * (9b²-25)=
=10/(9b²-25) * (9b²-25)=10
Скорость-4см/с
время-? с
расстояние- 28 см
28:4=7 (с)
Ответ:за 7 секунд.
Надеюсь что помогла! ☺
Ответ:
Пошаговое объяснение:
1)10 6/10-(7 3/10-y) =4 9/10
10 6/10-7 3/10+y=4 9/10
y=4 9/10+7 3/10-10 6/10
y=1 6/10=1 3/5
2)3 4/9-(x-1 7/9)=2 2/9
3 4/9-x+1 7/9=2 2/9
x=3 4/9+1 7/9-2 2/9
x=2 9/9=3
3)17 18/35-(n+4 23/35) =9 12/35
17 18/35-n-4 23/35 =9 12/35
n=17 18/35-4 23/35-9 12/35
n=3 18/35